Development of a rapid on-site nucleic acid detection method for new genotype muscovy duck parvovirus based on RPA-CRISPR/Cas12a - Liang, Qizhang; Chen, Wei; Wang, Weiwei; Liu, Rongchang; Fu, Qiuling; Fu, Guanghua; Cheng, Longfei; Jiang, Nansong; Chen, Hongmei; Huang, Yu (Frontiers in Veterinary Science, 2025)
New genotype Muscovy Duck Parvovirus (N-MDPV), a member of the Parvoviridae family, exhibits broad host tropism affecting Muscovy ducks, semi-Muscovy ducks, and white Kaiva duck. This pathogen causes severe morbidity and mortality in ducklings under 3 weeks of age, characterized by classic parvoviral lesions, beak atrophy, and growth retardation, posing substantial economic threats to China’s duck industry. To address diagnostic challenges, we developed an equipment-free detection platform targeting the conserved VP3 gene of N-MDPV. By integrating recombinase polymerase amplification (RPA) with CRISPR/Cas12a-mediated lateral flow strip (LFS) visualization, this method achieved isothermal amplification at 37°C within 35 min, eliminating dependency on thermocyclers. Validation experiments demonstrated exceptional sensitivity with a detection limit of 1.3 gene copies. Specificity testing revealed no cross-reactivity with eight common avian pathogens, confirming target exclusivity. Clinical validation using 98 field-collected duck tissue samples showed 98.98% concordance between our RPA-CRISPR/Cas12a-LFS and quantitative PCR. This study establishes the first CRISPR/Cas12a-based on-site diagnostic tool for N-MDPV, combining rapidity, sensitivity, accuracy and field-deployability.